Prescribing Physical Activity Through Primary Care: Does Activity Intensity Matter?. Issue 3 (September 2014) - Knight, Emily; Stuckey, Melanie I.; Petrella, Robert J.
Abstract: Background: Physical activity guidelines recommend engaging in moderate- and vigorous-intensity physical activity to elicit health benefits. Similarly, these higher intensity ranges for activity are typically targeted in healthy living interventions (ie, exercise prescription). Comparatively less attention has been focused on changing lower intensity physical activity (ie, sedentary activity) behaviors. The purpose of this study was to explore the effects of prescribing changes to physical activity of various intensities (ie, sedentary through exercise) through the primary care setting.Methods: Sixty older adults (aged 55–75 years; mean age 63 ± 5 years) volunteered to participate, and were randomly assigned to 4 groups: 3 receiving an activity prescription intervention targeting a specific intensity of physical activity (exercise, sedentary, or both), and 1 control group. During the 12-week intervention period participants followed personalized activity programs at home. Basic clinical measures (anthropometrics, blood pressure, aerobic fitness) and blood panel for assessing cardiometabolic risk (glucose, lipid profile) were conducted at baseline (week 0) and follow-up (week 12) in a primary care office.Results: There were no differences between groups at baseline ( P > 0.05). The intervention changed clinical (F(5, 50) = 20.458, P = 0.000, η P 2 = 0.672) and blood panel measures (F(5, 50) = 4.576, P = 0.002, η P 2 = 0.314) of cardiometabolic health. Post hoc analyses indicted no differences between groups ( P > 0.05).Conclusion: Physical activity prescription of various intensities through the primary care setting improved cardiometabolic health status. To our knowledge, this is the first report of sedentary behavior prescription (alone, or combined with exercise) in primary care. The findings support the ongoing practice of fitness assessment and physical activity prescription for chronic disease management and prevention.